Scientific ethical review committees in Dominican Republic. An analysis based on international ethical guidelines for biomedical research involving human beings - Canario Guzmán, Julio Arturo (Acta Bioethica, 2011)
The aim of this study is to describe the situation of scientific ethical review committees in Dominican Republic, in terms both their organization, composition, activities and training needs, and the level of following recommendations offered by International Ethical Guidelines for Biomedical Research involving Human Beings (2002). Seven scientific ethical review committees reporting activities during 2007 were included. A structure questionnaire elaborated based on “Complementary Guidelines to Survey and Evaluate Ethical Review Practices” developed by World Health Organization (2002) was used. Findings reveal the complexity of current situation of ethical review committees in Dominican Republic and the need to join efforts to achieve greater fulfillment of CIOMS guidelines recommendations.